(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Cajanus cajan (L) Millsp. is the perennial plant belongs to family Fabaceae, commonly called as Pigeon pea plant. The presence of phytoconstituents like flavonoids, the flavanone (substituted) from Cajanus cajan (L) Millsp. have in vitro neuroactive property. This flavanone named as pinostrobin helps to inhibit voltage – gated sodium channels. Because of its bioactive phytoconstituents it may act as antiepileptic drug. To avoid problems like ADR herbal plant might be alternative to treat epilepsy. The current study was therefore carried out to evaluate antiepileptic activity of Ethanolic extract of leaves of Cajanus cajan in rodents. The effect of ELECC in MES-induced convulsions in rat and PTZ-induced convulsion in mice was evaluated using doses 100 mg/kg and 200 mg/kg for 7 days. Phenytoin (25 mg/kg), Diazepam (4 mg/kg) was used as standard drug for respective model. Depending on the model, outcome measures were abolishment of Hind Limb Tonic Extensor phase in MES-induced convulsion in rat and onset of latency, recovery or death in PTZ-induced convulsion in mice as well as biochemical estimation of amino acid neurotransmitter (GABA, Glutamate) were evaluated. The ELECC at doses 100 and 200 mg/kg significantly delayed the HLTE phase in MES-induced convulsions in rat whereas, significantly increased onset of latency in PTZ-induced convulsion in mice. It also showed significant (p>0.0001) effect on the level of GABA and Glutamate in dose dependent manner in both models. The phytochemical study of C. cajan showed the presence of Glycosides, Flavonoids, Flavonones, Steroids, Tannins, Fixed oil, Fatty acids and Proteins. As the flavonoids present in C. cajan may contribute to the anticonvulsant activity of the plant. Therefore, the presence of such compounds in the extract may be responsible for the anticonvulsant effect. Therefore, present study validates its anticonvulsant activity. Further, research is required to elucidate its specific mechanism of action and isolation of responsible active principles.